"Who am I going to stay with? Who will accept me?": family‐level domains influencing HIV care engagement among disengaged adolescents in Kenya. Issue 2 (22nd February 2022) - Myers, Courtney; Apondi, Edith; Toromo, Judith J.; Omollo, Mark; Bakari, Salim; Aluoch, Josephine; Sang, Festus; Njoroge, Tabitha; Morris, Zariel; Kantor, Rami; Braitstein, Paula; Nyandiko, Winstone M.; et al.
Abstract: Introduction: Adolescents living with HIV (ALHIV, ages 10–19) have developmentally specific needs in care, and have lower retention compared to other age groups. Family‐level contexts may be critical to adolescent HIV outcomes, but have often been overlooked. We investigated family‐level factors underlying disengagement and supporting re‐engagement among adolescents disengaged from HIV care. Methods: Semi‐structured interviews were performed with 42 disengaged ALHIV, 32 of their caregivers and 28 healthcare workers (HCW) in the Academic Model Providing Access to Healthcare (AMPATH) program in western Kenya, from 2018 to 2020. Disengaged ALHIV had ≥1 visit within the 18 months prior to data collection at one of two sites and nonattendance ≥60 days following their last scheduled appointment. HCW were recruited from 10 clinics. Transcripts were analysed through thematic analysis. A conceptual model for family‐level domains influencing adolescent HIV care engagement was developed from these themes. Results: Family‐level factors emerged as central to disengagement. ALHIV‐particularly those orphaned by the loss of one or both parents‐experienced challenges when new caregivers or unstable living situations limited support for HIV care. These challenges were compounded by anticipated stigma; resultant non‐disclosure of HIV status to household members; enacted stigma in the household, with overwhelming effects on adolescents; or experiences of multiple forms of trauma, which undermined HIV care engagement. Some caregivers lacked finances or social support to facilitate care. Others did not feel equipped to support adolescent engagement or adherence. Regarding facilitators to re‐engagement, participants described roles for household disclosure; and solidarity from caregivers, especially those also living with HIV. Family‐level domains influencing HIV care engagement were conceptualized as follows: (1) adolescent living situation and contexts; (2) household material resources or poverty; (3) caregiver capacities and skills to support adolescent HIV care; and (4) HIV stigma or solidarity at the household level. Conclusions: Family‐level factors are integral to retention in care for ALHIV. The conceptual model developed in this study for family‐level influences on care engagement may inform holistic approaches to promote healthy outcomes for ALHIV. Developmentally appropriate interventions targeting household relationships, disclosure, HIV stigma reduction, HIV care skills and resources, and economic empowerment may promote adolescent engagement in HIV care.